Upaya Guru Madrasah Dalam Membentuk Kedisiplinan Pelajar Di Madrasah Aliyah Swasta Amaliyah Tanjung Tiga - Baihaqi (Nusantara Education, 2022)
This study describes the efforts of madrasa teachers in shaping student discipline at the private private madrasah aliyah, Tanjung Tiga. The purpose of this research is to provide information and education to readers that formal educational institutions, namely madrasas, have the ability to shape the character of being a disciplined student. This type of research is a qualitative research that seeks to explain social phenomena that are developing in the present mass. The data collection techniques used were observation and unstructured interviews and then the data were analyzed objectively and described scientifically by following the procedures for writing scientific papers. The results of the study were found as follows: First, private madrasah aliyah teachers in Tanjung Tiga on various occasions always educate students to always comply with the rules and regulations that apply in the madrasa environment. Second, the private madrasah aliyah teacher at Tanjung Tiga always provides an example of discipline for students to be a role model for him. Third, private madrasah aliyah teachers at tanjung three always carry out internal monitoring of student character and student discipline, if there are still students who are not disciplined, madrasa teachers do early identification of triggers for these students to become undisciplined Fourth, the head of private madrasa aliyah amaliyah tanjung three conducts evaluations periodically to all madrasah residents who aim to improve things that must be improved for the better the next day. Fifth, efforts to establish student discipline are carried out in persuasive ways.